Glomerular filtration rate in patients with renal space-occupying masses using combination of SPECT 99mTc-DTPA renal dynamic imaging and contrast-enhanced CT - Jia, Mingsheng; Jiang, Ling; Li, Xiujuan; Nie, Shengdong; Wang, Baojian (Frontiers in Oncology, 2026)
ObjectiveTo investigate changes in Glomerular Filtration Rate (GFR) and influencing factors in patients with renal space-occupying masses using a combination of single-photon emission computed tomography (SPECT) Tc-99m-labeled diethylenetriaminepentacetic acid (99mTc-DTPA) renal dynamic imaging and contrast-enhanced computed tomography (CT).MethodsFifty patients with renal masses underwent SPECT 99mTc-DTPA renal dynamic imaging and contrast-enhanced CT scans, and the GFR of the diseased kidney was compared with that of the contralateral healthy kidney in the same patient. The correlation between the size of the masses and the reduction in GFR was analyzed. Besides, the relationships between the net increment CT values in the renal parenchymal phase and excretory phase with the GFR changes were analyzed.ResultsThe GFR of diseased kidneys was significantly lower than that of the healthy kidneys (p < 0.05). There was no correlation between the size of the masses and the reduction in GFR (r=0.23, p>0.05). A negative correlation was found between the net increment CT value in the parenchymal phase and the decline in GFR (r=-0.38, p < 0.05), while there was no correlation between the net increment CT value in the excretory phase and the decline in GFR (r=-0.26, p>0.05).ConclusionThe blood supply characteristics observed in contrast-enhanced CT scans of renal masses can influence the calculation of GFR in radionuclide renal dynamic imaging. These characteristics should be taken into account when interpreting GFR results.